The Role of the School’s Principal in Improving Performance of School's Administration - Apriani, Wari (PPSDP International Journal of Education, 2023)
This study intends to identify, characterize, and assess the principal of SMP Negeri 4 Penukal Utara’s contribution to raising the caliber of school administration. The analytical method employs methods for descriptive quantitative analysis. In this study, information was gathered through interviews, observation, documentation, and literature reviews. According to the study’s findings, the principal of the school assumed the role of head of administration when performing administrative and informational administrative tasks. The school principal’s function as head of administration, together with the administrative staff’s performance, is carried out in line with operational requirements for school administration and positively affects how smoothly teaching and learning activities are carried out. The study’s conclusion is that the school principal’s position has ramifications for the execution of obligations and functions supporting the execution of operational tasks that facilitate the development of the school as a whole.